Depressed mood, suicidal behaviors, and health risk behaviors among youths in the Commonwealth of the Northern Mariana Islands: the 2017 CNMI Youth Risk Behavior Survey - Jennifer Lisa Sakamoto; Akira Shibanuma; Masamine Jimba (BMC, 2020)
Abstract Background The current study investigated the prevalence of depressed mood, suicide ideation, suicide plan, and suicide attempt and their associations with health risk behaviors among high school adolescents in the Commonwealth of the Northern Mariana Islands (CNMI). Methods This is a cross-sectional study analyzing self-reported data from the 2017 CNMI Youth Risk Behavior Survey (n = 1943). Modified Poisson regression models were used to identify the associations between 17 health risk behavior variables, including violence-related behaviors, substance use behaviors, sexual behaviors, and early risk-taking behaviors, and four variables related to depressed mood and suicidal behaviors. Results 40.7% adolescents reported being depressed, 25.0% reported suicide ideation, 22.8% reported formulating a suicide plan, and 13.6% attempted suicide. Female adolescents were more likely to report depressed mood and all included suicidal behaviors (p < 0.001). Being in a physical fight and forced sexual intercourse were associated with depressed mood, suicide ideation, suicide plan, and suicide attempt for both female and male adolescents. Use of "soft drugs" such as current smoking was associated with depressed mood (ARR = 2.33, 95% CI = 1.56-3.45, p < 0.001), suicide ideation (ARR = 1.23, 95% CI = 1.08-1.43, p < 0.001), suicide plan (ARR = 1.19; 95% CI = 1.05-1.35; p < 0.001), and suicide attempt (ARR = 1.18; 95% CI = 1.06-1.30; p < 0.001) for females, whereas use of "hard drugs" such as heroin was associated with depressed mood (ARR = 2.27, 95% CI = 1.37-3.85, p < 0.01), suicide ideation (ARR = 1.30, 95% CI = 1.01-1.67, p < 0.05), suicide plan (ARR = 1.82; 95% CI = 1.22-2.70; p < 0.01), and suicide attempt (ARR = 2.78; 95% CI = 1.47-5.26; p < 0.01) for male adolescents. Conclusion The prevalence of depressed mood, suicide ideation, suicide plan, and suicide attempt among CNMI adolescents was high, especially in female adolescents. While there were gender differences, many of the health risk behaviors were associated with depressed mood and suicidal behaviors. As sociodemographic factors are difficult to change, modifiable factors should be targeted to improve the mental health of adolescents.